The Past Forms of Japanese Futsuugo and Javanese Ngoko Lugu: Contrastive Analysis in Sociolinguistics - Teguh Santoso; Sulhiyah Sulhiyah (Universitas Diponegoro, 2020)
This paper is based on studying the differences and similarities in the form, structure, and usage of past sentences futsuugo-ngoko lugu in Japanese and Javanese. The study combines a qualitative and sociolinguistically informed comparative method. The data were taken from different sources, namely Shin Suikodenand Jin (a Japanese novel and play respectively), Ketoprak Wiswakarman (a traditional Javanese play), and Panjebar Semangat (a Javanese magazine), and were then analyzed from a contrastive linguistic perspective. Theories on Japanese and Javanese descriptive sentences, namely those of Ishii,[1] Masuoka,[2] Poedjosoedarmo,[3] Sasangka,[4] and Wedhawati,[5] were used. Besides, Djadjasudarma and Citraresmana [6] descriptive-qualitative method, Sanada’s,[7] concept of Sociolinguistics, as well as Tarigan’s,[8] Ishiwata and Takahashi’s,[9] theories of contrastive linguistics were also consulted. The study aimed to describe the differences and similarities in the forms, structures, and usage of past sentences futsuugo-ngoko lugu in Japanese and Javanese based on the dialogues' data. The study concludes that the addressers and addressees' speech levels in the Japanese conversations are those of futsuugo and ngoko lugu, which are comparable in the Javanese.